Perencanaan lanskap bantaran Tukad Unda sebagai waterfront park (studi kasus: Dam Lebah Kabupaten Klungkung) - Dewi, Ida Ayu Patni; Yusiana, Lury Sevita; Mayadewi, Ni Nyoman Ari (Jurnal Arsitektur Lansekap; Vol.5, No.2, Oktober 2019, 2019)
Landscape planning of the Unda riverbanks as waterfront park (case study: Lebah Dam, Klungkung). Tukad Unda is a river which has continuous flows and quite high rainfall, therefore, it is very potential to be developed, however it still has large destroying effects for the community if it is not well-managed. The planning of Tukad Unda’s Landscape as a waterfront park in Klungkung Regency is chosen as a topic in this research to identify and analyse the activities and facilities which is suitable with the development concept and the planning of Tukad Unda’s Landscape as a waterfront park that serves as a river conservation as well as recreational area for the nearby society. Research method used in this study is survey method with observational technique and literature survey. Stages of this study was a foundation in the planning-making includes the inventory, analysis and synthesis, and concept-making. The result showed that waterfront park in Unda River can give benefit to the surrounding people for green open space and social interaction space. The result of this study is expected to provide ideas to the society on how essential the rivers’ roles to the advancement of the environmental quality.